A cura di: Francesco Speciale

fomule di duplicazione
Noto $cos(2alpha)=2(sqrt2)/3$, calcolare $sin(alpha)$.


Svolgimento
Per le formule di duplicazione:
$cos(2alpha)=cos^2(alpha)-sin^2(alpha)$.
Nel nostro caso $cos(2alpha)=2(sqrt2)/3$, pertanto
$cos^2(alpha)-sin^2(alpha)=2(sqrt2)/3$;
ma $cos^2(alpha)=1-sin^2(alpha)$, sostituendo si ha:
$1-sin^2(alpha)-sin^2(alpha)=2(sqrt2)/3$;
$-2sin^2(alpha)=2(sqrt2)/3-1$;
$sin^2(alpha)=-2(sqrt2)/6+1/2$;
$sin^2(alpha)=1/2-(sqrt2)/3=(3-2sqrt2)/6 => sin(alpha)=sqrt((3-2sqrt2)/6)$.